TEACHING WRITING USING A DIGITAL CAMERA - Sartika, Dewi (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
Writing is one of the skills that students should master. Since writing is quite difficult for students to learn; therefore, the purpose of this study was to find out whether a digital camera had positive effects on students’ writing skill. There were thirty-three students involved in this study. The data were collected by interviewing the students and observing their writing works. It was found that teaching writing using a digital camera had positive effects on students’ writing skill. The students also gave good feedback to the teacher. The results of the students’ work were very excellent and they read their posters energetically. Moreover, the students were active, worked cooperatively, and had high spirit in writing posters using a digital camera.